KOMUNIKASI DUA ARAH DAPAT MERESPON PELAKU UKM DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK - Hiras Pasaribu; Asep Saefudin; Alp. Yuwidiantoro (Behavioral Accounting Journal, 2018)
Small and Medium Enterprises (SMEs) have limited resources, therefore it is necessary to mediate not only the understanding of taxation, but can help to develop business management, so that SMEs get the ease of developing the business and will have a positive impact on SME players. Thus Taxpayers will respond positively to tax pay compliance. This research will continue the development of SME governance. However, the first year of this study will first see the quality of education and understanding of the taxpayer, with the aim is, to determine the effect of the quality of extension services tax and tax understanding of the taxpayer compliance response. The method used is an eplanatory survey of 100 SMEs in Yogyakarta. To get data using questionnaire. By sending a questionnaire by post or e-mail, many respondents do not return it, then do it directly collect from the respondent. Data Testing is done by Partial Leas Squar (PLS) method. PLS does not assume any particular distribution for parameter estimation, so no parametric technique is required to test parameters. The result of this research conclude that the quality of service of tax service influence but very low to taxpayer compliance, while the understanding of taxpayer has a significant effect on taxpayer compliance.